SCOPE OF EDUCATION MANAGEMENT: RELATIONSHIP BETWEEN ORGANIZATION, ADMINISTRATION AND EDUCATION MANAGEMENT - Gimin; Achmad Nashrul Waahib; Baskoro Ajie (Adisam Publisher, 2025)
This study aims to examine in depth the scope of educational management with a focus on the relationship between the organization, administration, and management of education. These three components are considered the main pillars in managing an effective and efficient education system. The research method used is a literature study. The results of the study indicate that the organization, administration, and management of education have a close relationship and influence each other in the process of managing education. The organization acts as a fundamental structure that provides a framework for the implementation of educational activities, while the administration is responsible for the arrangement and coordination of operational processes within the organization. Educational management focuses on strategic planning, decision making, and control to ensure the achievement of educational goals optimally. The organization, administration, and management of education are three main pillars that cannot be separated in achieving educational goals. Each pillar has a specific role and function that complements and supports each other. Without good synergy between the three, the education system will not be able to function optimally.